Information networks among women and men and the demand for an agricultural technology in India - Magnan, Nicholas; Spielman, David J.; Gulati, Kajal; Lybbert, Travis J. (International Food Policy Research Institute, 2015)
Although there is ample evidence of differences in how and where men and women acquire information, most research on learning and household decisionmaking only considers access to information for a single, typically male, household head. This assumption may be problematic in developing-country agriculture, where women play a fundamental role in farming. Using gender-disaggregated social network data from Uttar Pradesh, India, we analyze agricultural information networks among men and women. We test for gender-specific network effects on demand for laser land leveling—a resource-conserving technology—using data from a field experiment that combines a Becker-DeGroot-Marschak (BDM) auction with a lottery.